1994
DOI: 10.1002/per.2410080203
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and structure of Hungarian personality traits

Abstract: This study reports on the application of the principles of the lexical approach to a non‐Indo‐European language, namely Hungarian. This language is a Uralic island surrounded on all sides by Indo‐European languages. In addition, the Hungarians are, in terms of cultural features, Europeans. These conditions provide a great opportunity for a crucial test case of the lexical approach to personality. Study 1 reports on the different phases of the selection of the trait terms from the Hungarian lexicon, a categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
2
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 30 publications
2
110
2
3
Order By: Relevance
“…We used factor analysis with principal component extraction and varimax rotation as is customary for validating the Big Five Inventory (Benet-Martinez & John, 1998;Denissen et al, 2008;Lang, Lüdtke, & Asendorpf, 2001;Plaisant, Courtois, Réveillère, Mendelsohn, & John, 2010;Szirmák & De Raad, 1994). Orthogonal rotations such as the varimax rotation are used when the factors are supposed to be uncorrelated or have low interfactor correlations.…”
Section: Factor Analytic Results and Comparison To Other Samplesmentioning
confidence: 99%
“…We used factor analysis with principal component extraction and varimax rotation as is customary for validating the Big Five Inventory (Benet-Martinez & John, 1998;Denissen et al, 2008;Lang, Lüdtke, & Asendorpf, 2001;Plaisant, Courtois, Réveillère, Mendelsohn, & John, 2010;Szirmák & De Raad, 1994). Orthogonal rotations such as the varimax rotation are used when the factors are supposed to be uncorrelated or have low interfactor correlations.…”
Section: Factor Analytic Results and Comparison To Other Samplesmentioning
confidence: 99%
“…In the five-factor solution, the Extraversion, Agreeableness, and Masculinity/ Emotional Stability factors remained much the same, whereas instead of Conscientiousness/Precision there was a Methodical Intellect factor and a second factor (also related to Conscientiousness) emphasizing Dependability; by loose standards, this solution resembles the AGB5. The six-factor solution produced a factor labeled Truthfulness that the investigators judged to be similar to the Integrity factor identified in Hungarian (Szirmák & De Raad, 1994). The investigators concluded that the Korean personality factors were quite similar to the Big Five, but clearly there were many divergences from the AGB5, both with respect to the axis locations of several factors and to the blends of clusters in Figure 1.…”
Section: Studies In Koreanmentioning
confidence: 91%
“…However, in both Italian studies, Agreeableness split into two distinct factors: One factor (Altruism, Tender-mindedness) included the Warmth, Generosity, and Integrity/ Sincerity clusters from Figure 1, and the other ("Quietness") included the Humility, Gentleness, and (reversed) Irritability clusters. Szirmák and De Raad (1994) reported the findings from lexical studies in Hungarian, a Finno-Ugric language. Over 8,000 person descriptors were extracted from dictionaries.…”
Section: Studies In Italianmentioning
confidence: 98%
“…Among emic studies, an Openness factor is not consistently extracted (De Raad, 1994; Di Blas & Forzi, 1998; Szirmák & De Raad, 1994). Furthermore, several emic studies have consistently yielded more than five factors (Almagor, Tellegen, & Waller, 1995; Benet-Martínez & Waller, 1997).…”
Section: Cross-cultural Studies Of the Big Fivementioning
confidence: 99%